2009
DOI: 10.1007/s12272-009-1115-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of 1-benzhydryl-sulfonyl-4-(3-(piperidin-4-yl) propyl)piperidine derivatives against pathogens of Lycopersicon esculentum: A structure-activity evaluation study

Abstract: Several 1-benzhydryl-sulfonyl-4-(3-(piperidin-4-yl)propyl)piperidine derivatives 8(a-j) were prepared by the treatment of substituted benzhydryl chlorides with 4-(3-(piperidin-4-yl)propyl)piperidine followed by N-sulfonation with sulfonyl chlorides in the presence of dry methylene dichloride and triethyl amine. The synthesized compounds were characterized by (1)H-NMR, IR, and elemental analysis. All the synthesized compounds were evaluated in vitro for their efficacy as antimicrobial agents by artificial inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Pharmacological agents containing a sulfonyl pharmacophore have been widely used as antibacterial, anticarbonic anhydrase, antiviral, and hypoglycemic agents 14–18 . Studies carried out by in vitro and/or in vivo approaches showed that sulfonyl derivatives shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological agents containing a sulfonyl pharmacophore have been widely used as antibacterial, anticarbonic anhydrase, antiviral, and hypoglycemic agents 14–18 . Studies carried out by in vitro and/or in vivo approaches showed that sulfonyl derivatives shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The piperidine nucleus is also an important moiety in medicinal chemistry research [16]. A number of piperidine ring containing chemical compounds have also been reported as antimicrobial agents [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The gradual development of pathogen resistance to routinely used pesticides demands a renewed effort to seek antimicrobial agents effective against pathogenic microbes (Vinaya et al, 2009). Furthermore, the use of combinations of pesticides with different modes of activity can delay the process of resistance development among these pathogens.…”
Section: Introductionmentioning
confidence: 99%